Treatment of Ramsay–Hunt's syndrome with multiple cranial nerve involvement and severe dysphagia: A case report. Issue 17 (April 2018) - Kim, Jong Min; Lee, Zeeihn; Han, Seungwoo; Park, Donghwi
Abstract: Rationale: Ramsay-Hunt's syndrome (RHS) is a disorder characterized by facial paralysis, herpetic eruptions on the auricle, and otic pain due to the reactivation of latent varicella zoster virus in the geniculate ganglion. A few cases of multiple cranial nerve invasion including the vestibulocochlear nerve, glossopharyngeal nerve and vagus nerve have been reported. However, there has been no report about RHS with delayed onset multiple cranial nerve involvement causing severe aspiration, and a clinical course that improved after more than one year of dysphagia rehabilitation and percutaneous endoscopic gastrostomy (PEG). Here, we report on a 67-year old male with delayed onset swallowing difficulty after 16 days of RHS development. Patient concern: Severe aspiration during swallowing. Diagnosis: Severe dysphagia caused by RHS with multiple cranial nerve involvement. Intervention: Application of percutaneous endoscopic gastrostomy (PEG) and rehabilitation therapy of dysphagia. Outcomes: After 13 months from symptom onset, his PAS improved from 7 to 2 in follow-up video-fluoroscopic swallowing study (VFSS). Then, he was re-admitted, and the PEG tube was removed and oral feeding was started. Lessons: This case gives us the lesson that optimal doses of acyclovir and corticosteroids are important to prevent progression of multiple cranial involvement in RHS, and swallowing difficulty in RHS patients with multiple cranial nerve involvement can be improved through long-term rehabilitation even if there is no improvement for more than one year.